The power of technology in the Bronze Age Eastern Mediterranean - Brysbaert, Ann, 19??- (Milton Keynes)
xiv, 258 sayfa, [12] sayfa resim
Keywords: “In the past, Bronze Age painted plaster in the Aegean and the Eastern Mediterranean has been studied from a range of different but isolated viewpoints. This volume brings both technological and iconographic approaches closer together by completing certain gaps in the literature on technology and by investigating how and why technological transfer has developed and what broader impact this had on the wider social dynamics of the late Middle and Late Bronze Age in the eastern Mediterranean.“ --